Life forms and shoot structure of the invasive species Geranium sibiricum l. (Geraniaceae) in two local populations in Ukraine - Kalista, M.S.; Kovalenko, O.A. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2024)
It was found out that the life form of the alien invasive plant species Geranium sibiricum is interpreted ambiguously in various literature sources, and in the description of underground organs (shoot and root systems), the statements of different authors are often even contradictory. Eighty individuals of G. sibiricum collected in 2019–2021 during field research in two local populations: in Pyriatyn town (Poltava Oblast) and Kyiv City (Kyiv Oblast) were revised by varying the type of growth form and shoot structures using the deep concept of the caudexes diversity and their differences from other structural formations. The basic life form and model of shoot formation of G. sibiricum, which is a biennial conode taproot monocarpic with monopodial branching type, were clarified. In the connection with the pronounced polyvariety of the species life form two more types of it were described in G. sibiricum individuals: caudex taproot oligocarpic and basiphys fibrousroot oligocarpic with sympodial type of branching. The structure of elementary inflorescences of G. sibiricum was analysed, the structure of its above-ground and underground shoot system, as well as the root system, was investigated. It was identified that G. sibiricum individuals in Pyriatyn town and Kyiv City populations differ in the length of the flowering shoot, the length of the internodes, and the level of branching, and they have different types of generative shoots according to their location in space. It was found that the diversity of the architectural structure of individuals of this invasive species, associated with different growth conditions, could probably be an adaptation to the specific environmental conditions of their populations and could be valuable for studying the introduction of invasive species and determining the developmental stages at which the management of their populations will be most effective.